Anatomical Properties of Flindersia pimenteliana F. Muell from Wondama Bay West Papua - Renny Purnawati; Imam Wahyudi; Trisna Priadi (Masyarakat Peneliti Kayu Indonesia, 2012)
Anatomical properties of Flindersia pimenteliana F. Muell wood from natural forest in Wondama Bay, West Papua was studied in order to analyze its general characteristic, anatomical structure and fiber quality. The microtome slides were prepared according to the Johansen's method, while the anatomical features observed according to the International Anatomist Wood Association (IAWA) List. The results showed that F. pimenteliana wood has decorative figure, white sapwood to pinkish and reddish brown heartwood, fine texture, straight grain, lustrous, good smell, moderately soft and light. The main characters of this species were growth ring indistinct, diffuse porous, simple perforation plate, vessels solitary and in radial multiples of 2-4 cells, inter vessel pits alternate, minute, vessel-ray pits with distinct borders, similar to inter vessel pit in size and shape,white deposit present in pores, axial parenchyma diffuse, scanty paratracheal and vascicentric, rays width 1-3 cells, prismatic crystals present in chambered axial parenchyma cells. Fiber length, diameter and wall thickness were 1,120.51, 19.22, and 2.66 μm, respectively. Fiber quality of F. pimenteliana could be classified into quality class II. Based on these properties, it could be recommended that this wood is suitable for wood craft, furniture, and cabinet work.Key words: anatomical structure, fiber quality, Flindersia pimenteliana, microtome slides